Legitimnost in odnosi v zaporskem okolju - Osterc, Zala (Teorija in praksa, 2024)
The article focuses on the dynamic nature of legitimacy in prisons and relations between prison actors. In a study conducted in the Ig prison for women in 2015 and 2023, 29 prisoners were interviewed. The analysis showed that prisoners perceive prison workers as legitimate powerholders and develop good relationships with them. Prisoners mentioned obtaining benefits and avoiding sanctions as primary reasons for cooperating. The findings showed differences in prisoners’ perception of fairness of prison workers in the periods under study, confirming the influence of the time component and specificity of the environment on the perception of prison staff’s legitimacy
Keywords: female prisoners; Ig prison; legitimacy; legitimnost; Legitimnost (politične vede); relations; Slovenia; Slovenija; zapor na Igu; Zapori; ženski zapori